Per- and polyfluoroalkyl substances impact human spermatogenesis in a stem-cell-derived model. (4th July 2018) - Steves, Alyse N.; Turry, Adam; Gill, Brittany; Clarkson-Townsend, Danielle; Bradner, Joshua M.; Bachli, Ian; Caudle, W. Michael; Miller, Gary W.; Chan, Anthony W. S.; Easley, Charles A.
ABSTRACT: Per- and polyfluoroalkyl substances (PFASs) represent a highly ubiquitous group of synthetic chemicals used in products ranging from water and oil repellents and lubricants to firefighting foam. These substances can enter and accumulate in multiple tissue matrices in up to 100% of people assessed. Though animal models strongly identify these compounds as male reproductive toxicants, with exposed rodents experiencing declines in sperm count, alterations in hormones, and DNA damage in spermatids, among other adverse outcomes, human studies report conflicting conclusions as to the reproductive toxicity of these chemicals. Using an innovative, human stem-cell-based model of spermatogenesis, we assessed the effects of the PFASs perfluorooctanesulfonic acid (PFOS), perfluorooctanoic acid (PFOA), perfluorononanoic acid (PFNA), and a mixture of PFOS, PFOA, and PFNA for their impacts on human spermatogenesis in vitro under conditions relevant to the general and occupationally exposed populations. Here, we show that PFOS, PFOA, PFNA, and a mixture of PFOS, PFOA, and PFNA do not decrease in vitro germ cell viability, consistent with reports from human studies. These compounds do not affect mitochondrial membrane potential or increase reactive oxygen species generation, and they do not decrease cell viability of spermatogonia, primary spermatocytes, secondary spermatocytes, or spermatids in vitro under the conditions examined. However, exposure to PFOS, PFOA, and PFNA reduces expression of markers for spermatogonia and primary spermatocytes. While not having direct effects on germ cell viability, these effects suggest the potential for long-term impacts on male fertility through the exhaustion of the spermatogonial stem cell pool and abnormalities in primary spermatocytes. Abbreviations: CDC: Centers for Disease Control; DMSO: dimethyl sulfoxide; GHR: growth hormone receptor; hESCs: human embryonic stem cells; PFASs: per- and polyfluoroalkyl substances; PFCs: perfluorinated compounds; PFNA: perfluorononanoic acid; PFOS: perfluorooctanesulfonic acid; PFOA: perfluorooctanoic acid; PLZF: promyelocytic leukemia zinc finger; ROS: reactive oxygen species; HILI: RNA-mediated gene silencing 2; SSC: spermatogonial stem cell